New information on Riograndia guaibensis Bonaparte, Ferigolo & Ribeiro, 2001 (Eucynodontia, Tritheledontidae) from the Late Triassic of southern Brazil: anatomical and biostratigraphic implications - Soares,Marina B. (2011)
The tritheledontid Riograndia guaibensis was the first cynodont described for the "Caturrita Formation" fauna from the Late Triassic of southern Brazil (Santa Maria 2 Sequence). The type materials did not preserve anatomical information regarding braincase, occiput, basicranium, zygomatic arch, postdentary bones and craniomandibular joint. Here new materials are described and supply the missing information. Riograndia shows a suite of important anatomical features quite derived among the non-mammaliaform eucynodonts, such as the partial closure of the medial orbital wall and braincase, extensive secondary osseous palate, wide primary palate, basicranium with jugular foramen separated from the periphery of fenestra rotunda, narrow zygomatic arch and much reduced postdentary bones. Many of these features constitute synapomorphies shared only with the other members of mammaliamorpha. Thus, the almost complete cranial, mandibular and dental information from the new fossils of Riograndia can bring a significant improve in the understanding of the anatomy and phylogenetic relationships of the tritheledontids and help to elucidate the transformational steps involved in the cynodont-mammal transition. Additionally, Riograndia is a key taxon in refining the "Caturrita Formation" biostratigraphy, enabling the connection of several fossiliferous outcrops that have a rich tetrapod fauna that can be correlated with other Triassic faunas from Gondwana and Laurasia.